2022
DOI: 10.1021/acs.jmedchem.2c00539
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Cyclic Peptide Inhibitors Targeting PD-L1 for Cancer Immunotherapy

Abstract: Blockade of the interaction between programmed cell death ligand-1 (PD-L1) and its receptor PD-1 has shown great success in cancer immunotherapy. Peptides possess unique characteristics that give them significant advantages as immune checkpoint inhibitors. However, unfavorable physicochemical properties and proteolytic stability profiles limit the translation of bioactive peptides as therapeutic agents. Studies have revealed that cyclization improves the biological activity and stability of linear peptides. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Cyclic peptides often exhibit superior biological activity compared to their linear counterparts due to their conformational rigidity and resistance to proteolytic degradation. , Additionally, the larger surface area of cyclic peptides leads to higher affinity and selectivity for protein targets . Biologically active cyclic peptides usually consist of amino acids (typically ≤10 aa) linked together to form a macrocyclic ring structure. Therefore, in this study, cyclic peptide OK2 or OK3 was synthesized by linking linear peptide K2 or K3 through head-to-tail cyclization, where an amide bond is formed between the amino and carboxy termini of each end (Figure A). Protein-based blocking efficiency and cellular ECM protein synthesis inhibition assays indicated that cyclic peptide OK2 exhibited similar blocking and inhibiting efficiency as linear peptide K2 , while cyclization of linear peptide K3 resulted in loss of bioactivity (Figure B,C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic peptides often exhibit superior biological activity compared to their linear counterparts due to their conformational rigidity and resistance to proteolytic degradation. , Additionally, the larger surface area of cyclic peptides leads to higher affinity and selectivity for protein targets . Biologically active cyclic peptides usually consist of amino acids (typically ≤10 aa) linked together to form a macrocyclic ring structure. Therefore, in this study, cyclic peptide OK2 or OK3 was synthesized by linking linear peptide K2 or K3 through head-to-tail cyclization, where an amide bond is formed between the amino and carboxy termini of each end (Figure A). Protein-based blocking efficiency and cellular ECM protein synthesis inhibition assays indicated that cyclic peptide OK2 exhibited similar blocking and inhibiting efficiency as linear peptide K2 , while cyclization of linear peptide K3 resulted in loss of bioactivity (Figure B,C).…”
Section: Resultsmentioning
confidence: 99%
“…The structural flexibility of linear peptides can make them susceptible to off-target binding, which limits their efficacy and increases the risk of adverse effects. 38 Cyclization has been shown in numerous studies to result in derivatives with a fixed geometry, thereby enhancing their selectivity to targets and proteolytic stability. 51 In this study, we chose to cyclize peptides K2 and K3 due to their optimal inhibitory activities against the CCN2/EGFR interaction in vitro.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…18,24 Cyclization also helps to stabilize the secondary structure of peptides [26][27][28] and can also improve binding affinity by reducing the entropy of the unbound state and therefore the entropy lost upon binding. 12,29,30 Computational protein design tools have matured over the last decade, enabling rational design of peptides with desired structure and function. 31 Molecular simulation has been used to assist in the design of a disulfide cyclized peptide that binds to PD1 and likely affects the PD1/PD-L1 checkpoint pathway.…”
Section: Introductionmentioning
confidence: 99%
“…18,24 Cyclization also helps to stabilize the secondary structure of peptides 26–28 and can also improve binding affinity by reducing the entropy of the unbound state and therefore the entropy lost upon binding. 12,29,30…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the HVP peptide is fully cleaved by serum enzymes in only 5 h [16]. Different methods have been investigated to confer stability toward enzyme cleavage, such as the introduction of non-natural amino acids [25] or by making peptide N-and C-termini less accessible to endoproteases (e.g., cyclization) [26]. Among the different strategies so far available, there is the possibility to change all L-amino acids (natural) with the corresponding D enantiomers in the reversed sequence of the original natural peptide.…”
Section: Introductionmentioning
confidence: 99%